Biodiversity and distribution patterns of planktonic cnidarians in San Matías Gulf, Patagonia, Argentina - Guerrero, Elena (2013)
The special location (40?42°S in the Southwestern Atlantic Ocean) and the hydrodynamic regime (limited water exchange with open ocean) in San Matías Gulf (Argentina) seem to produce a particular fauna of planktonic cnidarians whose their abundances are mainly shaped by the Gulf circulation. Four oceanographic cruises, covering 93 stations in three different seasons during 2007 and 2008 were carried out to quantify species richness and abundance, as well as to analyse the distribution of these cnidarians. We identified 20 species of hydromedusae and one siphonophore, increasing the total number of types of hydromedusae for the area to 23. This value is similar to the one found in the abutting Argentine continental shelf (20), but with a different assemblage com- position. Hydromedusae abundances found were low, except for a bloom of the Leptomedusa Obelia spp. during the cold season. The only siphonophore found in the area, Pyrostephos vanhoeffeni, has previously been thought to be endemic to Antarctic and sub-Antarctic waters, this being the first record for temperate waters of the Southwest Atlantic Ocean.